2013
DOI: 10.3390/agronomy3040816
|View full text |Cite
|
Sign up to set email alerts
|

Rhodococcus erythropolis and Its γ-Lactone Catabolic Pathway: An Unusual Biocontrol System That Disrupts Pathogen Quorum Sensing Communication

Abstract: Abstract:Rhodococcus erythropolis is an environmental Gram-positive Actinobacterium with a versatile metabolism involved in various bioconversions and degradations. Rhodococci are best known for their great potential in numerous decontamination and industrial processes. However, they can also prevent plant disease by disrupting quorum sensing-based communication of Gram-negative soft-rot bacteria, by degrading N-acyl-homoserine lactone signaling molecules. Such biocontrol activity results partly from the actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 114 publications
(131 reference statements)
0
36
0
Order By: Relevance
“…Although GBL was detected in Rhodococcus rhodochrous NCIMB 13064 culture medium, it was shown that GBL accumulated due to chemical oxidation of haloalkane in high cell density cultures ( Curragh et al, 1994 ). In silico analysis of the Rhodococcus erythropolis PR4 genome revealed the presence of genes encoding a communication molecule synthase, AfsA, and a communication molecule response regulator, ArpA with 31 and 36% amino acid sequence identity, respectively, suggesting the possible presence of a functional GBL-based quorum sensing system in this strain ( Latour et al, 2013 ). A similar analysis of the genome of Rhodococcus strain RHA1showed the presence of homologs for protein domains of both the GBL synthase and the receptor which suggests that GBL might play a role in this organism too ( Wuster and Babu, 2008 ).…”
Section: Quorum Sensing In the Phylum Actinobacteriamentioning
confidence: 99%
“…Although GBL was detected in Rhodococcus rhodochrous NCIMB 13064 culture medium, it was shown that GBL accumulated due to chemical oxidation of haloalkane in high cell density cultures ( Curragh et al, 1994 ). In silico analysis of the Rhodococcus erythropolis PR4 genome revealed the presence of genes encoding a communication molecule synthase, AfsA, and a communication molecule response regulator, ArpA with 31 and 36% amino acid sequence identity, respectively, suggesting the possible presence of a functional GBL-based quorum sensing system in this strain ( Latour et al, 2013 ). A similar analysis of the genome of Rhodococcus strain RHA1showed the presence of homologs for protein domains of both the GBL synthase and the receptor which suggests that GBL might play a role in this organism too ( Wuster and Babu, 2008 ).…”
Section: Quorum Sensing In the Phylum Actinobacteriamentioning
confidence: 99%
“…There are different strains of bacteria, fungi and yeasts species, mostly belonging to the genera Trichoderma, Bacillus, Pseudomonas and Streptomyces, which have demonstrated their effect as biocontrol agents and which are marketed for this purpose [16][17][18]. New purposes, like the ability of Rhodococcus erythropolis to prevent plant diseases by disrupting quorum sensing-based communication of gram-negative soft-rot bacteria, represent promising options for the future [19]. In addition, often, these microorganisms also act as phyto stimulants, which also reduces the use of chemical fertilizers with the consequent advantage from the economic and environmental point of view [20].…”
Section: Introductionmentioning
confidence: 99%
“…This species is best known for their great potential in numerous decontamination and industrial processes . They can also prevent biofilm formation by disrupting quorum sensing‐based communication . Furthermore, some species of Bosea are capable of oxidizing reduced inorganic sulfur compounds .…”
Section: Resultsmentioning
confidence: 99%